Genetic Diversity and Spatial Genetic Structure of an Epiphytic Bromeliad in Costa Rican Montane Secondary Forest Patches - Cascante Marín, Alfredo (2014)
Information on genetic variation and its distribution in tropical plant populations relies mainly on studies of ground‐rooted species, while genetic information of epiphytic plants is still limited. Particularly, the effect of forest successional condition on genetic diversity and structure of epiphytes is scanty in the literature. We evaluated the genetic variation and spatial genetic structure of the epiphytic bromeliad Guzmania monostachia (Bromeliaceae, Tillandsioideae) in montane secondary forest patches in Costa Rica. The sampling design included plants on the same trees (i.e., populations), populations within forest patches and patches within secondary forest at two different successional stages (early vs. mid‐succession). Six microsatellites revealed low levels of population genetic variation (A = 2.06, AE = 1.61, HE = 0.348), a marked deficiency of heterozygotes (HO = 0.031) and high inbreeding (f = 0.908). Genetic differentiation was negligible among populations within the same forest patch, but moderate (GST = 0.123 ± 0.043) among forest patches. Genetic relatedness between individuals was significantly higher for plants located within the same forest patch and separated by <60 m and decreased as distance between plants increased, becoming significantly negative at distances >400 m. An analysis of molecular variance (AMOVA) showed significant genetic variation between forest patches, but non‐significant variation between successional stages. The selfing breeding system and limited seed dispersal capabilities in G. monostachia could explain the observed levels and partitioning of genetic diversity at this geographic scale. However, these results also suggest that forest fragmentation is likely to influence the degree of local genetic structuring of epiphytic plants by limiting gene flow.